The Effect of Work-Life Balance and Workload on the Academic Performance of Working Postgraduate Students: The Mediating Role of Burnout - Wangi Lestari; Osly Usman (Journal of Digital Business and Global Economy, 2026)
Growing number of postgraduate student carrying employment duty alongside academic study create greater challenge in balancing professional responsibility, personal commitment, and educational demand, ultimately affecting Academic Performance. This research aim at investigation of effect from Work-Life Balance and Workload upon Academic Performance among working postgraduate student, with Burnout included a mediating variable. Quantitative approach together with causal research design receive application. Study involve 80 working postgraduate student in Jakarta selected through purposive sampling. Data collection occur through online questionnaire and analysis utilize SEM PLS. Finding reveal positive effect from Work-Life Balance toward Academic Performance and negative effect toward Burnout. In contrast, Workload show negative influence upon Academic Performance and positive influence upon Burnout. Burnout itself produce negative impact upon Academic Performance and mediate connection between Work-Life Balance and Academic Performance, together with connection between Workload and Academic Performance. Proposed model account for 59.4% variation within Academic Performance. Alignment with JD-R Theory was reinforced through these percussions, while simultaneously emphasizing the necessity of sustaining Work-Life Balance and regulating Workload for facilitating Academic Performance among employed postgraduate learners.